2002
DOI: 10.1111/1467-629x.t01-1-00074
|View full text |Cite
|
Sign up to set email alerts
|

The influence of corporate governance mechanisms on the quality of financial reporting and auditing: Perceptions of auditors and directors in Singapore

Abstract: This study uses two hypothetical cases to examine the perceptions of auditors and directors in Singapore about corporate governance practices relating to the quality of financial reporting and auditing. In the first case, the strength of the audit committee, the existence of an internal audit function and the strength of a corporate code of conduct were manipulated. All three variables were perceived to have some influence on financial reporting and audit quality. However, some interesting differences were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 23 publications
0
35
0
1
Order By: Relevance
“… Audit Committee: was computed by the presence of audit committee in the firm, coded 1 if there is an audit committee in the firm and coded 0 otherwise (Goodwin &Seow, 2002;Gulzar& Wang, 2011).…”
Section: International Journal Of Learning and Developmentmentioning
confidence: 99%
“… Audit Committee: was computed by the presence of audit committee in the firm, coded 1 if there is an audit committee in the firm and coded 0 otherwise (Goodwin &Seow, 2002;Gulzar& Wang, 2011).…”
Section: International Journal Of Learning and Developmentmentioning
confidence: 99%
“…According to Goodwin and Seow (2002) the Cadbury report published in 1992 recommended that the board of directors of a company should have a separate committee for overseeing the remuneration of executive directors and the auditing of the financial reporting. In other words, companies should have separate AC and remuneration committees.…”
Section: Audit Committee and Board Compositionmentioning
confidence: 99%
“…The same requirement is found under the Bursa listing requirements. Goodwin andSeow (2002), andBeasley et al (2000) found that investors, auditors and directors believe that a strong and effective AC is able to assist external auditors in auditing the fraudulent accounting records and increase the level of quality disclosure. Ho and Wong (2001) found that companies, which have an AC, are more likely to have a higher extent of voluntary disclosure.…”
Section: Audit Committee and Board Compositionmentioning
confidence: 99%
“…Studies have identified various triggers that encourage the occurrence of corporate fraud, such as external pressures on management to perform, opportunities for executives to deceive stakeholders and the absence of effective oversight (Goodwin and Seow, 2002;Graycar and Smith, 2002;Birchfield, 2004;and Davidson et al, 2005). A corollary of the corporate fraud and governance relation is that firms that have a high risk of corporate fraud react differently to improvements in governance than firms that are at low risk of fraud.…”
Section: Introductionmentioning
confidence: 99%